Sublimation Growth of Titanium Nitride Crystals - Du, Li; Edgar, James H.; Kenik, Edward A.; Meyer III, Harry (My University, 2010)
The sublimation-recondensation growth of titanium nitride crystals with N/Ti ratio of 0.99 on tungsten substrates is reported. The growth rate dependence on temperature and pressure was determined, and the calculated activation energy was 775.8±29.8kJ/mol. The lateral and vertical growth rates changed with the time of growth and the fraction of the tungsten substrate surface covered. The orientation relationship of TiN (001) || W (001) with TiN [100] || W [110], a 45o angle between TiN [100] and W [100], occurs not only for TiN crystals deposited on (001) textured tungsten but also for TiN crystals deposited on randomly orientated tungsten. This study demonstrates that this preferred orientational relationship minimizes the lattice mismatch between the TiN and tungsten.
Keywords: TiN; Sublimation growth; Tungsten substrate; Activation energy; Orientation